p90RSK modulates inter-and intracellular signaling in kidney diseases - Lin, Ling; Hu, Kebin (Frontiers in Cell and Developmental Biology, 2025)
The 90 kDa ribosomal s6 kinases (RSKs) are a group of serine/threonine kinases consisting of 4 RSK isoforms (RSK1-4), of which RSK1 is also named as p90RSK. p90RSK is directly phosphorylated and activated by its immediate upstream mediator extracellular signal-regulated kinase (Erk1/2), followed by activating various signaling pathways through phosphorylating selective downstream substrates. Aberrant induction of p90RSK has been reported in various human diseases including kidney disease suggesting a pathogenic role of p90RSK in these diseases. In response to pathogenic cues, p90RSK not only mediates intracellular signal events leading to cell-specific phenotypes but also modulates intercellular communication impacting the adjacent cellular responses. In this review, we provide an update on the current knowledge regarding the roles of p90RSK-mediated intercellular and intracellular signaling in the pathogenesis and progression of kidney diseases.